ANALISIS LAJU PERTUMBUHAN, EFEKTIVITAS DAN KONTRIBUSI PBB-P2 PADA PENDAPATAN ASLI DAERAH KOTA MANADO - Marselia Putri Pangarungan; Sonny Pangerapan; Priscillia Weku (Jurnal Riset Multidisiplin Edukasi, 2025)
This study aims to analyze the growth rate, effectiveness, and contribution of Rural and Urban Land and Building Tax (PBB-P2) to the Local Own-Source Revenue (PAD) of Manado City for the period 2020–2024. PBB-P2 is one of the regional taxes that plays a vital role in enhancing local fiscal independence. However, in Manado City, the realization of PBB-P2 revenue has not yet reached its full potential despite significant prospects. This research employs a qualitative descriptive approach, with data obtained through interviews and documentation from the Regional Revenue Agency (BAPENDA) of Manado City. The findings reveal that the growth rate of PBB-P2 is fluctuating and has yet to consistently reflect optimal performance. The level of effectiveness ranges from moderately effective to effective, while its contribution to PAD falls within the moderate category. These results indicate the need for improved taxpayer compliance and optimization of the taxable object database to enhance future PBB-P2 revenue performance.